2016
DOI: 10.1159/000450961
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Use of Uncovered Self-Expanding Metallic Airway Stents for Severe Expiratory Central Airway Collapse

Abstract: Background: Patients with severe symptomatic expiratory central airway collapse (ECAC) undergo a stent trial to determine whether they are candidate for tracheobronchoplasty. Most stent trials were done using silicone stents. However, there was a higher number of silicone stent-related complications. Objectives: The aim of this study was to evaluate the safety and efficacy of short-term uncovered self-expanding metallic airway stents (USEMAS) in patients with ECAC. Methods: This was a retrospective review. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Our group and others have used short-term (1-2 weeks) trials with silicone Y-stents and uncovered nitinol stents in an attempt to identify those patients who are more likely to benefit from surgical tracheoplasty (39,40). It is imperative to have a pre-procedural agreement with the patient that the stent(s) will only remain in place for 1-2 weeks given the potential complications of airway stents in benign disease.…”
Section: When the Stent Is Temporarymentioning
confidence: 99%
“…Our group and others have used short-term (1-2 weeks) trials with silicone Y-stents and uncovered nitinol stents in an attempt to identify those patients who are more likely to benefit from surgical tracheoplasty (39,40). It is imperative to have a pre-procedural agreement with the patient that the stent(s) will only remain in place for 1-2 weeks given the potential complications of airway stents in benign disease.…”
Section: When the Stent Is Temporarymentioning
confidence: 99%
“…We have recently shown that the short-term USEMAS trial improved respiratory symptoms, quality of life, and exercise capacity with few complications in patients with severe symptomatic ECAC. 28 As such, we currently adopted USEMAS to assess response in patients with severe symptomatic ECAC.…”
Section: Stent Trialmentioning
confidence: 99%
“…Patients undergo physiologic assessment with pulmonary function testing and a 6-minute walk test. Standardized questionnaires are also administered to determine functional status (Karnofsky Performance Scale); symptomatology [modified Medical Research Council (mMRC) dyspnea scale]; and quality of life assessment [respiratory impacted quality of life (St. George Respiratory Questionnaire)] and Cough Specific Quality of Life Questionnaire (CQLQ) (9,16,21,24).…”
Section: Preoperative Evaluation and Stent Trialmentioning
confidence: 99%
“…In some instances, the stent trial may prove inadequate or impossible to complete in patients with unusually large or small airways if correct stent sizes is not available, or in patients in whom their anatomy impedes rigid bronchoscopy for Y-stent placement (e.g., extreme cervical kyphosis). To lessen these potential confounding outcomes, our group recently has piloted the use of uncovered self-expanding metallic stents for short-term trials (24,27). Despite these limitations, a planned shortterm (<2 weeks) stent trial still may yield useful information about those patients with diagnosed TBM who may respond best to surgery.…”
Section: Preoperative Evaluation and Stent Trialmentioning
confidence: 99%